Predictive genetic testing in minors for Myocilin juvenile onset open angle glaucoma. (28th January 2015) - Souzeau, E.; Glading, J.; Ridge, B.; Wechsler, D.; Chehade, M.; Dubowsky, A.; Burdon, K.P.; Craig, J.E.
Abstract : Myocilin glaucoma is an autosomal dominant disorder leading to irreversible blindness, but early intervention can minimize vision loss and delay disease progression. The purpose of this study was to discuss the benefits of predictive genetic testing in minors for Myocilin mutations associated with childhood onset glaucoma. Three families with Myocilin mutations associated with an age of onset before 18 years and six unaffected at‐risk children were identified. Predictive genetic testing was discussed with the parents and offered for at‐risk minors. Parents opted for genetic testing in half of the cases. None carried the familial mutation. The age of disease onset in the family, the severity of the condition, and the age of the child are all factors that appear to influence the decision of the parent to test their children. Predictive genetic testing for early onset Myocilin glaucoma can facilitate early detection of disease or discharge from routine ophthalmic examinations.